Pola asuh orang tua pada remaja dengan kecanduan internet - Janet Tri Bibelia; Nur Oktavia Hidayati; Irman Somantri (Holistik Jurnal Kesehatan, 2021)
Parenting Style among Teenagers with an Internet Addiction Background: Teenagers are transition from childhood to adulthood which is a period of crisis against maladaptive risks, such as internet addiction. One of the external factors that most influences internet addiction in teenagers is parenting style.Purpose: To describe the parenting style among teenagers with an internet addiction.Method: A quantitative descriptive with a cross-sectional approach. The population was all students in grades of X and XI grade senior high school of Jatinangor, and samples were taken by purposive sampling with criteria of experiencing internet addiction, have complete parents, and living with parents with a total sample of 100 students. Data collection by using an instrument of Parental Authority Questionnaire (PAQ) which has translated in bahasa and tested for its validity with coefficient ≤ 0.300, and its reliability with of Alpha Cronbach ≤ 0.700. The results were analyzed by univariate.Results: The research showed that authoritative father’s parenting style perceived by teenagers (38%), authoritative mother’s parenting style perceived by teenagers (43%), authoritarian father’s parenting style perceived by teenagers (25%), authoritarian mother’s parenting style perceived by teenagers (28%), permissive father’s parenting style perceived by teenagers (28%), and permissive mother’s parenting style perceived by teenagers (16%).Conclusion: Most of the parenting styles perceived by adolescents with internet addiction are democratic maternal. Keywords: Internet addiction; Parent style; Teenagers. Pendahuluan: Masa remaja merupakan masa transisi dari anak-anak menuju  dewasa yang merupakan masa krisis terhadap risiko maladaptif, seperti kecanduan internet. Salah satu faktor eksternal yang paling mempengaruhi kecanduan internet pada remaja ialah pola asuh..Tujuan: Mengetahui gambaran pola asuh orang tua pada remaja dengan kecanduan internet.Metode: Penelitian deskriptif-kuantitatif dengan pendekatan cross sectional. Populasi pada penelitian ini ialah seluruh siswa kelas X dan XI SMA Negeri Jatinangor, sebanyak 838 siswa. Teknik pengambilan sampel adalah purposive sampling dengan kriteria inklusi mengalami kecanduan internet, orang tua lengkap dan tinggal bersama orang tua dengan jumlah sampel sebanyak 100 siswa. Pengumpulan data dilakukan dengan menggunakan Instrumen Parental Authority Questionnaire (PAQ) yang telah dialih bahasakan dan diuji validitasnya dengan nilai koefisien ≤ 0.300, serta reliabilitasnya dengan nilai Alpha Cronbach≤ 0.700. Hasil penelitian dianalisis  dengan teknik analisis univariat.Hasil: Hasil penelitian menunjukkan pola asuh ayah demokratis yang dipersepsikan remaja (38%), pola asuh ibu demokratis yang dipersepsikan remaja (43%), pola asuh ayah otoriter yang dipersepsikan remaja (25%), pola asuh ibu otoriter yang dipersepsikan remaja (28%), pola asuh ayah permisif yang dipersepsikan remaja (28%), dan pola asuh ibu permisif yang dipersepsikan remaja (16%).Simpulan: Sebagian besar pola asuh yang dipersepsikan remaja dengan kecanduan internet adalah pola asuh ibu demokratis.